EKSISTENSI NEGARA ISRAEL : (Telaah Atas Siyasah Syar’iyyah) - Tawakkal, Muhammad Iqbal; Zakirah (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2025)
This research aims to analyze the views of the siyasah syar'iyyah regarding the existence of the Israeli state and correlate it with basic concepts in state theory. The aim of this writing is to provide a comprehensive understanding of how the State of Israel exists. A study of Siyasah Syar'iyyah. This research uses an empirical juridical approach using primary data, namely research results and legislation, and secondary data, namely books and journals and analyzed qualitatively. The results of this research show that the Israeli state theory can be considered as a state entity that meets basic characteristics. However, when viewed from the perspective of state existence theory, Israel's existence and development are greatly influenced by security factors, national identity and regional conflicts. Most views in the context of Siyasah Syar'iyyah basically reject the establishment of the State of Israel. This is often due to the belief that Israel's founding involved the expulsion and suffering of the pre-existing Palestinian population.